2006
DOI: 10.1039/b607944j
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and electro-optical properties of spiro-bifluorenylvinylene-based polymers for light-emitting diodes applications

Abstract: Five new thermally robust electroluminescent arylenevinylene conjugated polymers, including poly[39,69-bis(3,7-dimethyloctyloxy)-9,99-spirobifluorenyl-2,7-vinylene] [(OC 10 ) 2 -Spiro-PFV] and poly[{39,69-bis(3,7-dimethyloctyloxy)-9,99-spirobifluorenyl-2,7-vinylene}-co-2-{methoxy-5-(2ethylhexyloxy)-1,4-phenylenevinylene}] [(OC 10 ) 2 -Spiro-PFV-co-MEH-PPV], were synthesized and used to fabricate efficient light-emitting diodes (LEDs). The glass transition temperatures of the polymers were found to be higher th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Figure 4 a shows the experimental spectra of the pseudoextinction coefficient, <k>, of the various samples. Spectra of H1 , H3 , H4 and H6 show six main peaks, at 2.6 eV (477 nm) due to the NB-CT transitions, at 3.14 eV (395 nm) related to the π–π* transitions of the conjugated molecule backbones, at 3.99 eV (311 nm),which is characteristic of triphenylamine-derivates [ 21 ], at 4.25 eV (292 nm) due to the vinyl-thiophene-derivates, and at 5.24 eV (234 nm) and at 5.91 eV (210 nm), due to thiophene- and benzene-derivates, respectively [ 22 , 23 ]. Spectra of H2 and H5 , on the contrary, show that the CT transition is shifted to lower energies, at 2.35 eV (528 nm), while the π–π* transitions of the conjugated molecule backbones is blue-shifted and damped.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 4 a shows the experimental spectra of the pseudoextinction coefficient, <k>, of the various samples. Spectra of H1 , H3 , H4 and H6 show six main peaks, at 2.6 eV (477 nm) due to the NB-CT transitions, at 3.14 eV (395 nm) related to the π–π* transitions of the conjugated molecule backbones, at 3.99 eV (311 nm),which is characteristic of triphenylamine-derivates [ 21 ], at 4.25 eV (292 nm) due to the vinyl-thiophene-derivates, and at 5.24 eV (234 nm) and at 5.91 eV (210 nm), due to thiophene- and benzene-derivates, respectively [ 22 , 23 ]. Spectra of H2 and H5 , on the contrary, show that the CT transition is shifted to lower energies, at 2.35 eV (528 nm), while the π–π* transitions of the conjugated molecule backbones is blue-shifted and damped.…”
Section: Resultsmentioning
confidence: 99%
“…The obtainment of PFVs is commonly pursued by three major synthetic strategies: the Wittig condensation, the Heck reaction, and the widely preferred Gilch route . Concerning the preparation of random fluorenylenevinylene copolymers, the properties of which have stimulated the interest of various research groups, as confirmed by a very recent work of Jin et al., the Gilch approach is the most versatile, because the Wittig condensation and the Heck reaction are mostly employed for synthesis of alternating PFVs copolymers. In this framework, we have recently proposed a versatile method for the obtainment of random PFVs by a one-pot Suzuki−Heck cascade reaction using potassium vinyltrifluoroborate as ethylene equivalent, and the suitable aryl dibromides.…”
Section: Introductionmentioning
confidence: 99%